2021
DOI: 10.1186/s40729-021-00296-0
|View full text |Cite
|
Sign up to set email alerts
|

Fractal analysis as a useful predictor for determining osseointegration of dental implant? A retrospective study

Abstract: Purpose The present study aimed at evaluating the effectiveness of fractal analysis on determining the osseointegration of dental implants. Material and methods In a single center, retrospective clinical trial, patients with dental implants in the mandibular premolar/molar region, ASA I–II and < 65-year-old patients were included. Orthopantomograph (OPG) were taken before implant surgery (t0), within a week of surgery (t1), and 1 (t2) and 2 (t3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…As a relatively simple technique that provides information about the complexity of the geometric structure of a surface, computer image analysis and the quantity, such as fractal dimension, can be used. Fractal and multifractal surface properties have so far been determined for many materials, including metallic materials and their alloys, ceramic, polymeric and amorphous materials [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. With this in mind, it can be assumed that the fractal analysis method can be a reliable and relatively simple method that may be used to compare the complexity and repeatability of slot surfaces of different orthodontic brackets.…”
Section: Introductionmentioning
confidence: 99%
“…As a relatively simple technique that provides information about the complexity of the geometric structure of a surface, computer image analysis and the quantity, such as fractal dimension, can be used. Fractal and multifractal surface properties have so far been determined for many materials, including metallic materials and their alloys, ceramic, polymeric and amorphous materials [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. With this in mind, it can be assumed that the fractal analysis method can be a reliable and relatively simple method that may be used to compare the complexity and repeatability of slot surfaces of different orthodontic brackets.…”
Section: Introductionmentioning
confidence: 99%
“… Heo et al (2002) also reported that FD decreased on the second day after orthognathic surgery and FD gradually increased over time. Soylu et al (2021) evaluated trabeculation around implants using fractal analysis on panoramic radiographs obtained in short-period intervals and concluded FD was significantly lower in first week measurements. This can be explained by the healing pattern of the bone.…”
Section: Discussionmentioning
confidence: 99%
“…The complexity of irregular objects may be represented by fractal dimension (FD) as a quantitative outcome [ 8 ]. In the literature, it is stated that the trabecular bone microarchitecture can be evaluated using fractal analysis on digital radiographic images [ 9 ]. FA on digital radiographs is not affected by alterations of exposure parameters or patient positions [ 10 , 11 ].…”
Section: Objectivesmentioning
confidence: 99%